Sistem Pendukung Keputusan Rekomendasi Aplikasi Pembuat Kuis Edukasi Untuk Pembelajaran Menerapkan Metode OCRA dan Pembobotan ROC - Jhiro Faran; Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Education quizzes are a form of interactive test or game designed to support the learning process in a fun and interactive way. Despite the availability of many applications for creating educational quizzes, users often face difficulties in selecting the ones that suit their learning needs and objectives. Therefore, this research suggests the use of a Decision Support System by implementing the OCRA and Weighted Rank Order Centroid (ROC) methods to recommend educational quiz maker applications. The ROC method is utilized to determine the weights or relative values of predefined criteria, thus facilitating the ranking process based on the importance of each criterion. Furthermore, the OCRA method is employed to analyze the operational competitiveness level of various alternative educational quiz maker applications. The research findings indicate that out of the 5 evaluated alternatives, ProProfs Quiz Maker scored the highest with a value of 1.515, making it the top choice for online learning media. Thus, the Decision Support System based on OCRA and ROC provides accurate recommendations for selecting educational quiz maker applications that align with learning needs and objectives.